Afta and economic growth: A study of the pioneering asean-5 members / James Paul - James, Paul (2016)

(untitled)
This thesis investigates empirically the causal relationship between changes in tariffs, and growth in Gross Domestic Product (GDP), inflows of net foreign direct investment (FDI), exports, and imports among the pioneering ASEAN-5 countries over the period of 1970 to 2013.The objective is to revisit the debate on tariff liberalization and the claims of its positive impact on these variables. The analysis is divided into two periods, i.e. the pre-AFTA (ASEAN Free Trade Zone) period of 1970-1992 and the AFTA period of 1992 to 2013.The ASEAN-5 of Indonesia, Malaysia, the Philippines, Singapore, and Thailand have experienced a trend decline in tariffs, and rapid GDP, net FDI inflows, export and import growth over the period 1970-2013. Apart from Singapore, the remaining countries did not show a significant relationship between tariff deregulation and GDP growth in all the periods. The relationship in Singapore was significant in the period 1992-2013. The results suggest that other factors have played a more significant role than tariffs in GDP growth in these economies. In addition, the general argument that the liberalization of tariffs will foster net FDI inflows is not supported by the evidence from Malaysia, the Philippines and Singapore. Indonesia and Thailand showed that tariff liberalization Granger caused net FDI inflows in the long period of 1970-2013. However, there was no evidence to show that changes in tariffs influenced growth in net FDI inflows in the periods before and following the introduction of AFTA in 1992. The evidence shows that the statistical relationship between tariff reduction and export growth is significant for Indonesia and Thailand, and the ASEAN-5 as a whole over the 1992-2013 and 1970-2013 periods. Interestingly, the CEPT mechanism from the AFTA process appears important in driving exports in Indonesia and Thailand. That relationship was only significant for Malaysia over the 1970-2013 periods at the 10 percent level. Also, there was no evidence of a significant relationship between tariffs and exports in the Philippines and Singapore. There is no statistical evidence of a relationship between changes in tariffs and import growth in Indonesia, the Philippines and Thailand among the ASEAN-5. While it may be necessary for policy makers in Indonesia, the Philippines and Thailand to be concerned over the impact of tariff deregulation on import growth, such a sudden surge in imports could be a consequence of deregulation targeted at attracting FDI into the previously protected sector of automobile assembly and automotive components. While the statistical evidence is robust we have not controlled for the counterfactual, which is not possible using data. Overall, the results show a significant impact of tariff deregulation particularly on net FDI inflows, exports and imports in Indonesia and Thailand. However, the results also show that deregulation is not a panacea for stimulating rapid economic growth. In contrast to the claims of mainstream economics, several other factors matter, including government policy and the success they enjoy in stimulating structural change from low to high value added activities.